Determining factors in the performance of hiking in dinghy sailing: a literature review - Chicoy Garcia, I.; Encarnación Martinez, A. (European Journal of Human Movement, 2015)
The aims of this study were to identify and analyse the research studies related to the sailing technique "hiking", as well as analysing the influential factors in this technique. The data was obtained from an analysis carried out on nine databases, limiting the investigation to the period between 1975 and 2013. The articles analysed in this review collected physiological, biomechanical, training variables, literature reviews and other studies that serve to show the technique in depth. Hiking is considered the most decisive technique in the performance of a boat dinghy with middle and high winds, which is aerobic and dynamic in nature, due to the constant movement that the sailor must perform while hiking to counterbalance the ship's movements. The quadriceps muscle is the most important for maintaining the position of hiking, being the muscle that reaches the higher percentage of maximum voluntary contraction (% MVC) and suffers more stress due to the high restriction of oxygen and perfusion associated with their high level of isometric work; while the knee is the joint that does more work, because of the higher moments of force applied during the action of hiking. As for the types of training, no specific training on this technique has achieved results applicable to practice.